Analytic, Paradoxical, and Synthetic Sentences on ABC and The Hard Way Song Lyrics - Frans Sayogie; Difa Mahya; Dyona Priorita Dwiarso (Insaniyat : Journal of Islam and Humanities, 2019)
This research aims to identify and classify; analytic, paradoxical, and synthetic sentences which are logical types of sentences in the song lyric of  ABC by The Jackson 5 and The Hard Way by The Kinks in order to get the virtue of meanings of the lyrics.  The method used in this research is descriptive qualitative by analyzing and comparing the data by using Kant’s containment concept. The data used in this research are lyrics from the songs ABC 5 and The Hard Way. The research findings obtained: one analytic sentence in ABC, one paradoxical sentence in The Hard Way and twenty two synthetic sentences in both lyrics. The data indicate that there are more synthetic sentences rather than analytical and paradoxical sentences in the songs. In conclusion, the synthetic sentences used on the song lyrics are more fabricated for the virtue of meanings on the song lyrics than analytic and paradoxical sentences. Therefore, the listeners can express their emotions freely by song lyrics using synthetic sentences.